Friday

July 25, 2014

July 25, 2014

Posted by **pavatharani** on Wednesday, August 3, 2011 at 11:51am.

prove that

x^3-2x^2-7x+5=3

- maths -
**Reiny**, Wednesday, August 3, 2011 at 1:19pmstart with the equation:

x^3 - 2x^2 - 7x + 2 = 0

after two tries, I found x = -2 to be a solution

so it factors to

(x+2)(x^2-4x+1) = 0

from the second ...

x = (4 ± √12)/2 = 2 ± √3

but you told me x = 1/(2-√3)

rationalizing this ...

1/(2-√3) * (2+√3)/(2+√3)

= (2+√3)/(4 - 3) = 2 + √3

which is one of the values for x I got by solving the equation.

**Related Questions**

maths - If the sum of the squares of the roots of the quadratic equation ax^2 + ...

Advanced Maths (Vectors) AQA Level - Triangle ABC with D, E and F the midpoints ...

Advanced Maths (Vectors) AQA Level - Triangle ABC with D, E and F the midpoints ...

DISCRETE MATHS - Prove that for every set S, Ø \subseteq( S. i need to Use ...

Maths - X and Y are points on the sides BC and AC of a triangle ABC respectively...

Maths - prove that 2+2=5

maths - prove that: 1/1+x^b-a + x^c-a + 1/1+x^a-b +x^a-c = 1

maths - prove that : 2^n + 2^n-1 / 2^n+1 - 2^n = 3/2

maths - If a+b+c=0 then prove that a^4+b^4+c^4=2(a^2b^2+b^2c^2+c^2a^2)

maths - prove that 2 2 2 2 (n-1) + n + (n+1) = 3n +2